An Integrated Approach for Extraction of Carbonate Rocks Based on Landsat OLI Data: a Case Study around Stone Forest, Southwest China – Upgrading for Land-use Planning Purposes. Issue 4 (December 2020) - He, Ping; Cheng, Xianfeng; Mao, Zifei
Abstract: Geological remote sensing information extraction of the lithology has always been the hotspot and difficulty in remote sensing applications. Carbonate rocks covered more than 3.4 million km 2 in China. The study area is located around Stone Forest, which is World Natural Heritage. Sedimentary rocks distributes mainly in the area, and their spectral characteristics are complex and difficult to be recognized by remote sensing. Landsat OLI data was selected as the information source. The false color synthesis, principal component change, band ratio and other processing technologies of OLI data were applied to the lithological enhancement identification of carbonate rocks. Selected information will be used to improve the quality of the land-use planning.